173k views
2 votes
Rewrite the equation by completing the square. 4 x^{2} -12 x +9 = 04x 2 −12x+9=0

User Art Taylor
by
4.7k points

2 Answers

7 votes

Answer:(x-3/2)^2 =0

Explanation:

User AntonyM
by
5.0k points
7 votes

Answer:

(2x -3)^2 = 0

Explanation:

In this particular instance, the square is already complete. The rewrite is to show that.

(2x -3)^2 = 0

__

In the general case, ...

(ax +b)^2 = a^2x^2 +2abx +b^2

Comparing this form to the given left-side expression, we see that ...

a = 2, b = -3

So, the trinomial is already a perfect square trinomial.

User Dileet
by
5.1k points